Cultivating consciousness: Unveiling TikTok’s detrimental effects on youth mindset and behaviour - Sofia Hayati Yusoff; Suria Hani A. Rahman; Rosidayu Sabran; Fauziah Hassan; Rosninawati Hussin; Nurhilman Hizami Shamsol Baharin (TAYLORS UNIVERSITY, 2025)
Index by Scopus (Tier 2)